This preview shows pages 1–7. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: m a = m b ~ v = ~ v f a + ~ v f b and v 2 = v 2 f a + v 2 f b ~ v ~ v = ( ~ v f a + ~ v f b ) ( ~ v f a + ~ v f b ) v 2 = v 2 f a + v 2 f b + 2 ~ v f a ~ v f b v 2 f a + v 2 f b = v 2 f a + v 2 f b + 2 ~ v f a ~ v f b ~ v f a ~ v f b = Since ~ v f a ~ v f b = 0, the angle between ~ v f a and ~ v f b is 90 1...
View
Full
Document
This note was uploaded on 10/17/2011 for the course PHYSICS 7A taught by Professor Lanzara during the Spring '08 term at University of California, Berkeley.
 Spring '08
 Lanzara
 Physics, Mass

Click to edit the document details